Experimental dissolution of carbonaceous materials in water at 1 GPa and 550°C: Assessing the role of carbon forms and redox state on COH fluid production and composition during forearc subduction of organic matter - Toffolo, Luca; Tumiati, Simone; Villa, Alberto; Fumagalli, Patrizia; Amalfa, Andrea; Miozzi, Francesca (Frontiers in Earth Science, 2023)
Biogenic carbonaceous material (CM) is the main carrier of organic carbon in the subduction zone and contributes to COH fluid production and volcanic arc gaseous emissions. Here we investigated the effect of the structural, textural and chemical heterogeneity of CM on its reactivity and redox dissolution by conducting short-lived (1h) experiments, where synthetic analogues of CM (ordered graphite, graphite oxide (GO), mesoporous carbon (MC), Vulcan® carbon (VC) and glass-like carbon (GC)), are reacted with water at P = 1 GPa and T = 550 °C – conditions typical of a warm forearc subduction – and fO2 buffered from ΔFMQ ≈+4 to –7. We show that the amount of dissolved CM (CMdissolved) and the proportion of volatile carbon species (Cvolatile) in the fluid is related both to the structure and the peculiar surficial properties of the carbon forms, such as carbon sp2- and sp3-hybridization, amount of oxygen heteroatoms, presence of oxygenated functional groups (OFGs) and of active sites. MC and graphite (C(sp2) >93 at%, O <1 at%, OFG <2.3 at%, high proportion of active sites) are relatively inert (CMdissolved <0.4 mol%) but the former reacts more extensively at extreme redox conditions (producing CO2+CO and CO2+CH4 Cvolatile mixtures at ΔFMQ ≈+4 and –7, respectively), while the latter has a maximum of Cvolatile production (CO2 + CH4) at ΔFMQ ≈0, which is not observed in a 10-day long run; partly-ordered GO (C(sp3) >98 at%, O ~31 at%, OFG ~41 at%) is the most reactive material at all redox conditions (CMdissolved >2.6 mol%) and produces CO2 as the dominant Cvolatile species; disordered GC and VC (C(sp3) <30 at%, O <8 at%, OFG <30 at%) are more reactive at ΔFMQ ≈ +4 (CMdissolved ~1 mol%) and ΔFMQ ≈–7 (CMdissolved >1 mol%), where Cvolatile is dominantly CO2 and CH4, respectively. Besides the significant deviations from thermodynamically predicted graphite-saturated COH fluid composition and speciation, our results suggests that: (1) immature CM (disordered, rich in C(sp3), O, OFGs) is preferentially dissolved under high fluid fluxes and may buffer fluids to rather oxidizing conditions; (2) a descending flux of oxygen (and hydrogen) bond to CM may exist.